From the right to higher education to the challenge of access for all - Wessler Boneti, Lindomar; Gisi, Maria Lourdes; Filipak, Sirley Terezinha (Revista Diálogo Educacional, 2013)
Analyzes how the conceptual meanings and purposes of higher education in educational policies are expressed at different times in Brazilian history, a project typically bourgeois to the access for all. It is argued that beyond the institutional framework (rules, norms, values etc.) governing the making of higher education, which has remained unchanged throughout the historical period of the Brazilian educational policies, continuing to be tuned to bourgeois ethics, different events (political, economic, cultural etc.), in different historical moments, they have contributed to significant changes on the feature of higher education policies in relation to its purpose and conceptual meanings, such as: higher education associated with the idea of social evolution, using the bourgeois culture as a parameter order, before calling "Bourgeois Revolution" in Brazil; The focus on community has higher education as a tool for building a national project, after the "Bourgeois Revolution"; the return to the focus on the individual and on competitiveness from the discourse of citizenship and social inclusion, beginning with the last two decades of the twentieth century, moving towards its main challenge: access for all.